Konsep Fithrah: Potensi dan Kualifikasi Perbuatan Manusia - Hayati Hayati; Vanila Nur Sela (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Human beings are regarded as special creations because they are endowed with an innate nature (fitrah), various potentials, and responsibility for their actions. Understanding these three aspects is essential to explain the position of human beings as servants of Allah and as khalifah (vicegerents) on earth. This study aims to examine the concepts of human fitrah, human potential, and the classification of human actions from an Islamic perspective. The study employs a library research method by examining relevant sources, including books, scholarly journals, and other supporting documents. Data were analyzed qualitatively using a deductive approach, beginning with general concepts to draw specific conclusions. The findings indicate that fitrah represents the basic nature of human beings, including an innate tendency to recognize and worship Allah and to accept the values of truth. Human beings are also endowed with various potentials, including intellectual, spiritual, qalb (heart), and physical potentials, which need to be developed in a balanced manner through education and life experiences. In Islam, human actions are classified into five categories: obligatory (wajib), recommended (sunnah), permissible (mubah), discouraged (makruh), and prohibited (haram), which serve as moral guidelines in life. Understanding the concepts of fitrah, human potential, and the classification of actions enables human beings to live responsibly and achieve balance among the spiritual, intellectual, and social dimensions.